Delivering safe, comfortable, and connected pedestrian and bicycle networks: a review of international pratices. - (:unkn) unknown (My University, 2015)
The purpose of this study was to identify noteworthy and innovative international designs, treatments, and other practices that have potential to improve bicycle and pedestrian safety and access and increase walking and bicycling in the United States. This report covers treatments and practices from a total of 11 countries, covering six thematic areas: (1) network infrastructure, (2) limited auto traffic areas, (3) signalization, traffic control, and intelligent transport systems, (4) policy change, (5) criteria or methods for prioritizing improvements, and (6) goals and network performance measures. A number of treatments and practices appear to have significant potential to help improve bicycle and pedestrian network safety, comfort, and connectivity in the U.S. Additional study and actions are needed to better understand, test, and refine the most promising designs and practices for use by U.S. jurisdictions.
Keywords: Individualverkehr; Fahrradverkehr; Fußgängerverkehr; Infrastruktur; Mobilität; Verkehrsplanung; Verkehrssicherheit; Radverkehrsführung; Radverkehrssicherheit; Fahrradinfrastruktur; Netzwerk; Studie